2016
DOI: 10.1158/2326-6066.cir-15-0184
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Cetuximab-Mediated Antibody-Dependent Cell Cytotoxicity in Metastatic Colorectal Cancer Patients Predicts Treatment Efficacy

Abstract: Cetuximab is a monoclonal antibody to the EGFR that induces antibody-dependent cell cytotoxicity (ADCC) through Fcg receptors on immune cells. Although SNPs in genes encoding Fcg receptors are functionally relevant to cetuximab-mediated ADCC in colorectal cancer, a direct correlation between in vitro ADCC and clinical response to cetuximab is not defined. We therefore enrolled 96 consecutive metastatic colorectal cancer (mCRC) patients at diagnosis in a study that assessed FcgR status and cetuximab-mediated AD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 49 publications
1
54
0
Order By: Relevance
“…The efficacy of mAb treatment, including that of Cetuximab, is influenced by FCγR polymorphism (184). The homozygous genotype of valine at position 158 on the FcγRIIIa receptor (158 V/V genotypes), as opposed to the 158 V/F or 158 F/F FcγRIIIa genotypes is often, but not always, associated with improved clinical outcomes (185)(186)(187)(188)(189). Moreover, FCγ receptor affinity is impacted by patterns of antibody glycosylation (190) and by particular IgG variants.…”
Section: Clinically Utilized Mabs-recent Evidence Of Nk Cell Contribumentioning
confidence: 99%
“…The efficacy of mAb treatment, including that of Cetuximab, is influenced by FCγR polymorphism (184). The homozygous genotype of valine at position 158 on the FcγRIIIa receptor (158 V/V genotypes), as opposed to the 158 V/F or 158 F/F FcγRIIIa genotypes is often, but not always, associated with improved clinical outcomes (185)(186)(187)(188)(189). Moreover, FCγ receptor affinity is impacted by patterns of antibody glycosylation (190) and by particular IgG variants.…”
Section: Clinically Utilized Mabs-recent Evidence Of Nk Cell Contribumentioning
confidence: 99%
“…In the present study, the in vivo and in vitro experiments confirmed that the antibody portion of an ADC drug (Cetuximab) served as a vector for the effector molecule (tubulin inhibitor MMAE) to bring MMAE to the targeted tumor tissue. The small molecule cytotoxic cytokines play use high cytotoxicity to kill local cells, while monoclonal antibodies can also maintain their own antibody-dependent cytotoxicity (ADCC) or Fc-mediated complement-dependent cytotoxicity (CDC) to exert their own effects [ 15 ]. This method combines their strengths and complements their weaknesses, and they can exert a strong anti-tumor effect, reduce damage to normal tissues and cells, and also the antibody resistance problem [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we previously reported that patients affected by mCRC with high NK-cell cytotoxicity, independently from the type of therapy, showed a significantly higher response rate and a longer progression-free survival (PFS) compared with patients with low NK-cell cytotoxicity[ 9 ]. Due to the complex and dynamic nature of the immune system we are evaluating the hypothesis that decrease over time of NK cell activity could associate with progression of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The issue is very complex since the interactions between components of the immune system and tumor cells are largely unknown. We recently reported that polymorphisms of receptors involved in ADCC (antibody-mediated cellular cytotoxicity) as well as the NK cells activity of patients affected by mCRC were predictive and prognostic[ 9 ]. Additionally, MDSCs (myeloid-derived suppressor cells) and Tregs (regulatory T-cell) are a component of the immune system that may promote tumor progression[ 10 ] by inhibiting both innate and adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%